Impact of a Local Low-Cost Ward-Based Response System in a Canadian Tertiary Care Hospital - Andrea Blotsky; Louay Mardini; Dev Jayaraman (Critical Care Research and Practice, 2016)
Background. Medical emergency teams (METs) or rapid response teams (RRTs) facilitate early intervention for clinically deteriorating hospitalized patients. In healthcare systems where financial resources and intensivist availability are limited, the establishment of such teams can prove challenging. Objectives. A low-cost, ward-based response system was implemented on a medical clinical teaching unit in a Montreal tertiary care hospital. A prospective before/after study was undertaken to examine the system’s impact on time to intervention, code blue rates, and ICU transfer rates. Results. Ninety-five calls were placed for 82 patients. Median time from patient decompensation to intervention was 5 min (IQR 1–10), compared to 3.4 hours (IQR 0.6–12.4) before system implementation (p<0.001). Total number of ICU admissions from the CTU was reduced from 4.8/1000 patient days (±2.2) before intervention to 3.3/1000 patient days (±1.4) after intervention (IRR: 0.82, p=0.04 (CI 95%: 0.69–0.99)). CTU code blue rates decreased from 2.2/1000 patient days (±1.6) before intervention to 1.2/1000 patient days (±1.3) after intervention (IRR: 0.51, p=0.02 (CI 95%: 0.30–0.89)). Conclusion. Our local ward-based response system achieved a significant reduction in the time of patient decompensation to initial intervention, in CTU code blue rates, and in CTU to ICU transfers without necessitating additional usage of financial or human resources.